Echeveria sotoi (ser. Gibbiflorae, Crassulaceae), a new species from coastal Michoacán, Mexico - Rosales-Martínez, C. Santiago; Quirarte-Tejeda, Jaime A.; Hernández-Campos, J. Daniel (Phytotaxa, 2024)
E. sotoi (ser. Gibbiflorae, Crassulaceae) is described as a new species endemic to the coast of Michoacán, Mexico. It is morphologically similar to E. gibbiflora, from which it differs by having a generally taller but much thinner stem, narrower and oblanceolate to oblanceolate-obovate leaves without purplish-glaucous colourations, thinner peduncles, horizontally spreading to obliquely ascending cincinni, flowers with frequently longer corollas but usually shorter sepals, and narrower nectary scales. The species was assessed as Critically Endangered (CR) following the IUCN criteria. A distribution map is provided for the species of E. ser. Gibbiflorae native to Michoacán.